(untitled) (International Journal of Engineering and Computer Science, 2023)
The research paper focuses on two crucial aspects: Artificial Intelligence (AI) and Machine Learning (ML). These emerging technologies have significant implications for social welfare. AI involves developing computer systems that can perform tasks requiring human intelligence, while ML enables machines to learn from data and improve their performance without explicit programming. AI and ML are crucial because they have the potential to revolutionize industries, automate tasks, enhance decision-making, and bring about social benefits in areas like healthcare, finance, education, and the tech industry that rely heavily on AI and ML (Margetts, 2022; Auernhammer, 2020). The primary research inquiry explores the intricate ways these technologies can be harnessed to propel social progress, all while considering the broader spectrum of opportunities and challenges entailed in their development and implementation, drawing upon existing research. The second research question focuses explicitly on the design of ChatGPT—an eminent AI application—and examines how it embodies human values such as honesty, integrity, and peace and its social responsiveness concerning diversity, inclusivity, equity, and ethical considerations. The initial segment of the research focuses on unraveling the potential contributions of AI and ML to social welfare. By undertaking an extensive review and synthesis of current literature, this paper identifies the manifold applications of these technologies across diverse domains, encompassing healthcare, education, environmental sustainability, and social justice. This comprehensive analysis sheds light on the potential benefits, such as enhanced decision-making, heightened efficiency, and augmented accessibility while also recognizing the associated challenges like algorithmic bias, privacy concerns, and ethical deliberations (Zajko, 2021). By delving into the current state of research, this paper aims to provide an encompassing comprehension of the opportunities and challenges arising from the development and utilization of AI and ML technologies for the betterment of society. The subsequent portion of the research places particular emphasis on ChatGPT—an influential AI application—and endeavors to examine its design in relation to human values and social responsiveness. This paper delves into how the system embodies values such as honesty, integrity, and peace. Moreover, this study examines the system’s inclusivity, diversity, equity, and ethical considerations, evaluating its responsiveness to the prompts provided, its capacity to avoid biased responses, and adherence to ethical guidelines. This analysis strives to offer insights into the strengths and limitations of ChatGPT’s design and to foster a comprehensive understanding of its impact on societal values and social interactions. The research findings significantly contribute to the burgeoning field of AI and ML for social welfare by illuminating these technologies’ potential benefits and challenges. Additionally, the analysis of ChatGPT’s design provides valuable insights for AI developers and policymakers, empowering them to cultivate responsible AI systems that align with human values and address societal needs effectively.